Imunoexpressão das claudinas -1 e -7 em ameloblastomas e germes dentais humanos - Iglesias, Déborah Pitta Paraíso (2008)
We investigated the immunohistochemistry expression of claudins -1 and -7 in ameloblastoma and in human dental germs on the pattern of distribution (focal, regional or diffuse), the cells that expressed (if central or peripheral) and the location of that expression in the cell components recital membrane, cytoplasm and nucleus. Among the 29 cases of ameloblastoma, 24 were type solid and 6 unicystic. In 7 mandibular specimens of human fetuses found dental germs from the stage of bud to the crown. We note that the pattern of expression in the dental germs was variable for claudinas studied according to the cell type and stage of differentiation and was invariate only in the cells of stellate reticulum. In epithelium internal of enamel organ, claudin-1 has been decreasing with the progression of differentiation as to claudina-7 that was found in the cells of the peripheral papilla. For ameloblastoma the expression was more significant than that observed in dental germs. Fisher s exact test no found association between the expression of claudinas cells in central and peripheral and the type of ameloblastoma (solid or unicystic). Thus, in general the claudin-1 was positive in the central cell of 93,1% of the cases and in peripheral cells of 51,7%. The claudin-7 was expressed in the cells of all cases central and peripheral cells from 89,7%. For both claudins the distribution was predominantly diffuse cells both in central and peripheral cells. Given our findings it is suggested that the expression of claudins may be indicative of the involvement of these molecules in morphogenetics events culminating with the dental development and that possibly influence the development of neoplastic ameloblastoma